Nutritional and non-communicable disease (NCD) status association with fall among older persons in Malaysia : findings from National Health and Morbidity Survey (NHMS) Malaysia 2018 - Jayvikramjit Singh,; Mohamad Fuad Mohamad Anuar,; Azli Baharudin,; Suhaila Abdul Ghaffar,; Cheong, Siew Man; Lalita Palineveloo,; Syafinaz Mohd Sallehuddin,; Nur Shahida Abd Aziz,; Norsyamlina Che Abdul Rahim,; Munawara Pardi,; Nur Hamizah Nasaruddin,; Ahmad Ali Zainuddin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Fall is a health problem for older persons. This study investigates the potential factors of concern: the nutritional status of older persons and non-communicable disease association with incidence of falls. This study used data from NHMS 2018, and conducted a cross-sectional design by applying two-stage stratified cluster sampling. Descriptive statistics such as the percentage of each variable were done. Factors associated with falls were determined at both univariate and multivariable levels using simple logistic regression and multiple logistic regression. The data were presented as standard values for each analysis and adjusted odds ratios with 95% CI with p values (<0.05). A total of 3,867 from 3,977 elderly (mean age 68.2+ 6.85) were recruited with the response rate of 97.2%. Factors associated with fall were 70 years old and above (AOR= 1.34, 95% CI: 1.09, 1.64), obesity (AOR=1.55, 95% CI: 1.21, 1.98), undernutrition (AOR=1.59, 95% CI: 1.30, 1.94), persons with 2 NCDs (AOR=1.49, 95% CI: 1.15, 1.92) and persons with 3 NCDs (AOR=1.63, 95% CI: 1.23, 2.16). Advanced age, malnutrition, obesity, and having two or more NCDs are associated with falls in the NHMS 2018 study. In conclusion, falls are prevalent among older persons. There is an urgent need for public health strategies and programmes to decrease the incidence of modifiable risk factors and early identification of those at risk. Implementation of fall preventive programs which includes multifactorial interventions at hospitals and homes can also significantly reduce incidence of falls among older persons.